Mechanisms In The Relation Between Religion And Health With Emphasis On Cardiovascular Reactivity To Stress - Masters, Kevin S. (Research in the social scientific study of religion, 2008)
There is evidence of a relation between religiosity and health. Some of the strongest support for this relationship is found among markers of cardiovascular functioning and related pathologies (e.g., primary hypertension). The specific behavioral, social, and psychophysiological mechanisms that influence this relationship have not been thoroughly tested in empirical studies. A general model of mechanisms through which religiosity and spirituality may influence health is presented followed by specific elucidation of the possible role of cardiovascular reactivity to stress as a link between religiosity and cardiovascular functioning. Preliminary supportive empirical evidence for this pathway is also provided. Investigators are encouraged to use this model as a guide when conducting investigations on religion and health and to specifically explore how religion may influence psychological processes that in turn influence cardiovascular functioning as a response to varying stressors.